1999
DOI: 10.1006/jcph.1999.6344
|View full text |Cite
|
Sign up to set email alerts
|

On a Wind-Driven, Double-Gyre, Quasi-Geostrophic Ocean Model: Numerical Simulations and Structural Analysis

Abstract: The main objectives of this paper are to adapt an efficient and accurate spectralprojection method for a wind-driven, double-gyre, mid-latitude, quasi-geostrophic ocean model, and to study the double-gyre phenomenon from numerical and structural analysis points of view. A number of numerical simulations are carried out and their structural stability and structural transition/bifurcation are investigated using a new dynamical systems theory of two-dimensional incompressible flows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Along a similar line of research, Maddison et al [14] used refined numerical grids to investigate the effect of potential vorticity fluxes on the dynamics of the double-gyre system by decomposing eddy potential vorticity fluxes into divergent and rotational components. Another example of highfidelity simulations for the double-gyre problem can be found in [15] which applied highorder spectral elements for numerical accuracy.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Along a similar line of research, Maddison et al [14] used refined numerical grids to investigate the effect of potential vorticity fluxes on the dynamics of the double-gyre system by decomposing eddy potential vorticity fluxes into divergent and rotational components. Another example of highfidelity simulations for the double-gyre problem can be found in [15] which applied highorder spectral elements for numerical accuracy.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Although forced by a steady wind, such a model configuration is not stationary for this viscosity value, as circulation is characterized by an oscillating behavior with formation of smaller scale vortices and shifting of main current patterns. In fact, DG circulation shows a bifurcation (Shen et al, 1999), identified by a critical value of the Reynolds number: for values lower than it, the flow converges quickly to an unique steady state solution, which is 10 structurally stable, while above that value, instabilities occur and the symmetry of the structure between sub-polar and sub-tropical cells is broken. The vertical turbulent mixing is parameterized by coefficients of vertical viscosity and diffusion of 1 m 2 /s; a linear bottom friction is introduced with a coefficient of bottom drag of 8x10 -7 m/s.…”
Section: The Twin Model Experimentsmentioning
confidence: 99%
“…[20]) with an implicit treatment of the rotational term to avoid stability constraint by the strong rotation, one need to solve, at each time step, the following system of two secondorder equations:…”
Section: Problems With Variable Coefficients In One Directionmentioning
confidence: 99%